Zion im 1. Makkabäerbuch = Zion in 1 Maccabees - Oepping, Florian (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2025)
The article examines the references to Zion in 1 Maccabees as well as the other mentions of the mountain (1 Macc 4:46; 11:37; 13:52 and 16:20). First Maccabees 4:46 can be identified as an editorial addition. For 1 Macc 11:37, narrative reasons can be asserted that allow an insight into the authors’ world of thought. First Maccabees 13:52 and 16:20, on the other hand, raise further questions regarding the ending of the book. Basically, three specific motifs can be identified by systematising the passages: The march to Zion, fortification, and proclamation. However, all evidence are primarily place references. The analysis not only allows some conclusions to be drawn about the developmental scheme of the term "Zion" but also raises new doubts about it., AbstractThe article examines the references to Zion in 1 Maccabees as well as the other mentions of the mountain (1 Macc 4:46; 11:37; 13:52 and 16:20). First Maccabees 4:46 can be identified as an editorial addition. For 1 Macc 11:37, narrative reasons can be asserted that allow an insight into the authors’ world of thought. First Maccabees 13:52 and 16:20, on the other hand, raise further questions regarding the ending of the book. Basically, three specific motifs can be identified by systematising the passages: The march to Zion, fortification, and proclamation. However, all evidence are primarily place references. The analysis not only allows some conclusions to be drawn about the developmental scheme of the term "Zion" but also raises new doubts about it.